(untitled) (Iranian Journal of Kidney Diseases, 2013)
Bacterial infections are common in patients with nephrotic syndrome, including peritonitis, sepsis, meningitis, urinary tract infection, and cellulitis. An 8-year-old boy presented with colicky abdominal pain, vomiting, swollen and painful erythematous lesions around the umbilicus and in anterior surface of left thigh (cellulitis), mild generalized edema, and ascites. The microorganism isolated from peritoneal fluid and blood cultures was Pneumococcus. Association of pneumococcal sepsis, peritonitis, and cellulitis has been rarely reported in nephrotic syndrome.